2013 IEEE 4th International Conference on Cognitive Infocommunications (CogInfoCom) 2013
DOI: 10.1109/coginfocom.2013.6719285
|View full text |Cite
|
Sign up to set email alerts
|

Regional properties of global communication as reflected in aggregated Twitter data

Abstract: Twitter is a popular public conversation platform with world-wide audience and diverse forms of connections between users. In this paper we introduce the concept of aggregated regional Twitter networks in order to characterize communication between geopolitical regions. We present the study of a follower and a mention graph created from an extensive data set collected during the second half of the year of 2012. With a k-shell decomposition the global core-periphery structure is revealed and by means of a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…By means of aggregation of their different forms of connections we created two different communication networks: the mention (M) and the follower (F ) networks Here we show two regional graphs based on [2]. We created the two graph representations, F and M, as weighted and directed graphs.…”
Section: Regional Graph Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…By means of aggregation of their different forms of connections we created two different communication networks: the mention (M) and the follower (F ) networks Here we show two regional graphs based on [2]. We created the two graph representations, F and M, as weighted and directed graphs.…”
Section: Regional Graph Propertiesmentioning
confidence: 99%
“…A comparative analysis of intra-regional and interregional communication ties can reveal structural properties, and be indicative of the information flow on the network. [2] We examine empirical centrality measures of nodes. First, we consider their generalized weighted degrees, or volume of directed communication ties as follows.…”
Section: Regional Graph Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing availability of digital traces of human activity provide unprecedented opportunity for researchers to study complex phenomena in society [1][2][3][4][5][6]. Data mining methods that preform unsupervised extraction of important features in large datasets are especially appealing because they enable researchers to identify patterns without making a priori assumptions [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Lerman et al[6] specifically extracted social networks of active users on Digg and Twitter, and tracked how interest in news stories spreads among them, they also showed that social networks play a crucial role in the spread of information on these sites, and that network structure affects dynamics of information flow. Kallus et al[7] introduced the concept of aggregated regional Twitter networksand characterized the communication between geopolitical regions. Liu et al [8] built a specific agent-based model using NetLogo based on the propagation model of SIR by taking consideration of the unique property of twitter-like websites in information flow, max spread time and the mechanism of people believing the rumor.…”
mentioning
confidence: 99%